Enhancing graduate employability and the need for university-enterprise collaboration - Abdelghafoor, Nedal Fayez (Journal of Educational and Psychological Sciences, 2021)
This study is adapted translation to a desk study of Tran, Thi Tuyet (2016) which addressed enhancing graduate employability and the need for university- enterprise collaboration. The researcher used the procedures of the analytical descriptive method, for that it was based mainly on the original study, and some other Arabic and foreign references, to clarify some issues , concepts and terms covered in the original study. The study aimed to highlight the issue of enhancing graduate employability, and the need for cooperation of universities with Operating institutions, therefore, the study focused on clarifying the concept of graduate employability as covered in related literature, then tried to define the justifications of universities’ cooperation with the operating institutions. it also tried to review the forms of this cooperation and its benefits, after that the study shed light on the most prominent challenges facing this cooperation, Finally the researcher presented a set of recommendations and solutions that may contribute to enhancing graduate employability, addressed to universities, the private sector, governments and researchers.